The liability of natural and legal persons for violating European Union restrictive measures in Latvia, Romania, the Netherlands, Germany and France - Pundure, Ance Renāte (Riga Graduate School of Law, 2024)
response to its actions in Ukraine. The events of February 2022 have prompted the EU to react and significantly expand the list of sanctioned individuals and entities. In the context of these developments, the question of penalties applicable in EU Member States for sanctions violations has been widely discussed. Existing legislation across Member States is not uniform. In some countries, fines for breaches of EU sanctions are disproportionately low. One of these countries is Romania, where the fine for sanctions violations is around EUR 6,000, accompanied by the confiscation of property involved in or resulting from the violation. Recently, a directive has been adopted to address this problem. However, it should be noted that it took many years to prevent existing loopholes.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; sanctions; restrictive measures